EVALUASI HOMOGENITAS TANAMAN HASIL PRODUKSI BENIH F1 MENTIMUN YANG MENGGUNAKAN GALUR GYNOECIOUS DAN MONOECIOUS - U. Sumpena (MEDIAGRO, 2013)
Homogenity evaluation of plant that results from F1 cucumber seed production wich use Gynoecious line and Monoecious. The aim of the research are to get information about seed production tecnic of F1 hybrid cucumber seed which efficient and can quaranted high level of homogenity, quality, and seed yield. This research was conducted at trial field of Lembang Vegetable Research Institut from Februari – November 2012. Randomized Complicy Block Design with three replications was used, population 20 plans / plot. F1 seed material was evaluated is result from 2 result research before. In 2011 about effectively of Gynoecious and male or female row rasio at hybrid cucumber seeds production. The result showed that hybrid cucumber seed production with Gynoecious better than with Monoecious. Hybrid cucumber seed production with Gynoecious incrased fruit set, assure true type of hybriditation from two parents depend on qualitation character homogenity. Application at field hybrid seed production with Gynoecious line can maximize pure pollination by insect pollinater with I know parent mal row female parent compotition. Key words: Cucumber, evaluation, gynoecious, homogen.